Indicaciones éticas en las revistas de educación indexadas en la WoS - Díaz-Campo, Jesús; Segado-Boj, Francisco (El Profesional de la Información, 2017)
Se investiga la presencia de indicaciones éticas en las directrices para autores y revisores de 214 revistas de la categoría Educación e Investigación en Educación de los Journal Citation Reports de 2014. Se ha empleado un análisis de contenido y temático para examinar qué principios aparecen recogidos y cómo se abordan. Un 11,2% de revistas no incluye ningún tipo de directriz y existe una presencia desigual de los diferentes principios éticos en el resto. Los más abundantes son los criterios para establecer el plagio (63,01%) y la redundancia o duplicación de publicaciones (67,12%). Las responsabilidades éticas de los revisores (7,76%) y las sanciones (3,20%) por conducta poco ética tienen una presencia mínima.
Ethical guidelines in Educacion & Educational Research journals indexed in the WoS
The presence of ethical guidelines in the instructions for authors and reviewers from 214 journals indexed in the Education and Educational Research category of the 2014 edition of the Journal Citation Reports is analyzed. Content and thematic analysis methodology has been followed to examine the presence of topics regarding ethics of scholarly publishing and research. According to the results, 11.2% of the analyzed journals do not include mentions of any ethical topic and the presence of the various subjects studied differs among the rest. The most frequent are criteria for determining plagiarism (63.01%) and duplicate publication (67.12%). Ethical responsibilities of reviewers (7.76%) and sanctions for misconduct (3.20%) have a low presence.
Keywords: ética de la investigación; políticas de control; publicaciones científicas; educación; plagio; conflicto de intereses; falsificación de datos; autoría; revisores; autores; research ethics; control policies; scholarly publishing; education; plagiarism; conflict of interest; data falsification; authorship; authors; reviewers; JCR; Scopus